LYMPHOCYTIC MASTOPHATY PRECEDING BILATERAL PRIMARY BREAST LYMPHOMA: CASE REPORT - Cavalcante, Jéssica Moreira; Goursand, Mauro Henrique Muniz; Pires, Douglas de Miranda; Clarke, Paula; Oliveira, Fernanda Silveira de (Mastology, 2021)
Introduction: Lymphocytic mastopathy is a rare condition, responsible for 1% of all benign breast lesions, commonly associated to autoimmune disorders and diabetes (especially insulin-requiring diabetes). The differential diagnosis may be difficult, since the clinical and imaging aspects can mimic malignant disease. Some authors suggest that lymphocytic mastitis could be a precursor of primary breast lymphoma. However, other studies disagree with such correlation, present-ing the mastopathy as a distinct diagnosis, but one of difficult differentiation from lymphoma. To avoid misdiagnosis, an appropriate study of the specimen is recommended, through image-guided or surgical biopsy and immunohistochemical markers. Due to its unique presentation and scarce reports in global literature, we present a case of a patient with lym-phocytic mastopathy that preceded the diagnosis of primary bilateral lymphoma. Case report: A healthy 46-year-old, nulliparous, premenopausal female patient, with a negative family history of breast cancer, presented palpable masses in the inferior medial quadrants (IMQ) of the right and left breasts, measuring 5 cm and 1.2 cm, respectively, both classified as Category 4 in the BIRADS lexicon. She was referred for excisional surgical biopsy, with anatomopathological diagno-sis compatible with nonspecific chronic mastitis in both specimens. Immunohistochemistry (IHC) revealed lymphocytic mastitis, without signs of malignancy. The patient maintained regular control with a mastologist and after two years of follow-up, two new category 4 masses were identified: one in the IMQ of the right breast, and another in the retro-areolar (RRA) region of the left one. Core biopsy of the masses revealed lymphoproliferative disease, with IHC showing non-Hodg-kins’ diffuse large B-cell lymphoma, (Ki67 60%, CD20+, BCL6+). A magnetic resonance imaging of the breasts identified bilateral breast masses in the RRA region, with extension to the medial quadrants and no cleavage plane with the nipple, the largest measuring 4.5 cm, in the left breast, with heterogeneous internal enhancement and type III kinetic pattern, in addition to an atypical lymph node in level I of the right axilla. Positron emission tomography–computed tomography (PET-CT) ruled out distant disease, and confirmed it was restricted to the breasts. The patient received six cycles of che-motherapy with cyclophosphamide, doxorubicin, vincristine, and prednisone, presenting a complete metabolic response on PET-CT. Subsequently, radiotherapy was performed on both breasts at a dose of 30 Grays in 15 fractions each and, after a clinical follow-up of two months, no new abnormalities have been noted.